Gendered Pathways: How Mathematics Ability Beliefs Shape Secondary and Postsecondary Course and Degree Field Choices - Perez-Felkner, Lara; Nix, Samantha; Thomas, Kirby (Frontiers in Psychology, 2017)
Do mathematics ability beliefs explain gender gaps in the physical science, engineering, mathematics, and computer science fields (PEMC) and other science fields? We leverage U.S. longitudinal, nationally representative data to estimate gendered differences in girls’ and boys’ perceptions of mathematics ability with the most difficult or challenging material. Our analyses examine the potentially interacting effects of gender and these ability beliefs on students’ pathways to scientific careers. Specifically, we study how beliefs about ability with challenging mathematics influence girls' and boys' choices to pursue PEMC degrees, evaluating educational milestones over a six year period: advanced science course completion in secondary school and postsecondary major retention and selection. In doing so, we review our recently published findings and present additional findings further demonstrating gender differences in secondary school mathematics ability beliefs in relation to objective ability measures and the consequences of these beliefs for students’ chosen degree fields.